Perception of the COVID-19 pandemic and situation of the specialized training among medical interns in the Community of Navarre - de Carlos Artajo, Joaquin; Zabalza San Martin, Lucia; Sola Galarza, Amaya; Rubio Vela, Tomás; Duart Clemente, Julio; Beaumont Caminos, Carlos; Forga Llenas, Lluis; Teijeira Alvarez, Rafael (Spanish Journal of Medical Education, 2022)
Medical model in Spain is carried out through the specialized training system. The aim of this study is to analyze the opinion of the Medical Interns in Residency (MIR) of the Autonomous Community of Navarra in three areas: consequences derived from COVID-19, training program and future job prospects among last-year residents. Cross-sectional observational study using a voluntary and anonymous online survey, shared interns from Navarra, carried out between April-May 2021. A total of 228 responses were recorded from 553 MIR residents in Navarra. Seventy-eight percent of the residents have carried out some activity related to the COVID, with 97% of them appreciating some degree of deterioration in their training and 96% having suffered a negative emotional impact. 68% would like to continue working at the same center at the end of their training period, with 79% considering the recruitment system to be inadequate. The COVID-19 pandemic has impaired the training of MIRs, altering teaching itineraries, rotations, reducing surgeries and generating a negative emotional impact. Most of the residents have carried out activities related to COVID-19, although most of them consider that it is not necessary to extend their training time. Most residents would like to continue working at the center where they have been trained, although this demand is not matched by the supply available after completing this training period. In addition, recruitment method has little support from the residents.